2015
DOI: 10.15835/nsb.7.4.9649
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Differentiation Studies among Natural Populations of <i>Tilapia zillii</i>

Abstract: The population structure of Tilapia zillii (Gervais 1848) from three reservoirs in Nigeria, Osun State (Opa, Osu and Igun) was determined by employing morphological and molecular (Random Amplified Polymorphic DNA) methods. For morphological studies, 25 morphometric measurements and six meristic counts were recorded on 40 individuals within each population. Principal Component Analysis (PCA) was performed on the morphometric and meristic data using the PAST software. For RAPD studies, genomic DNA was extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…However, Oladimeji et al (2015) found that lower jaw width was the character most responsible for variation among the three wide populations of T. zillii studied.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, Oladimeji et al (2015) found that lower jaw width was the character most responsible for variation among the three wide populations of T. zillii studied.…”
Section: Discussionmentioning
confidence: 83%
“…This is in contrast with the report by Solomon et al (2015) where the meristic counts on C. gariepinus overlapped so widely among the sexes from different culture environments, so that the populations could not have been discriminated by sex or by culture environment. Oladimeji et al (2015) also reported that the PCA diagram of the meristic counts done on Tilapia zillii showed no specific pattern of differentiation among three natural populations.…”
Section: Discussionmentioning
confidence: 98%
“…Th e meristic counts, however, overlapped broadly showing no divergence among the populations. Also, Oladimeji et al (2015) reported that all the clusters produced by the Principal components analysis (PCA) on the morphometric and meristic characters of T. zillii, overlapped revealing a low level of diff erentiation among the three populations studied. Although the studied populations are the same species, little or no gene fl ow had occurred among them which may be due to their locations.…”
Section: Discussionmentioning
confidence: 99%
“…PCA on the morphometric and meristic data were evaluated. Population centroids with 95 % ellipses obtained from the PCA scatter diagram were used to observe relationships among populations (Turan et al, 2005;Oladimeji et al, 2015;Ola-Oladimeji et al, 2016). PCA loadings were used to show the traits with the highest variation within the population Ola-Oladimeji et al, 2016) using the unweighted Pair Group Method with Arithmetic mean for phenogram or dendrogram grouping reported by Sneath and Sokal (1973).…”
Section: Methodsmentioning
confidence: 99%
“…According to Goncalves et al, [19], Froese and Pauly [20], Mohammed [21] and Mwanja et al, [22], morphological change and divergence within species are expected to take place when fishes are exposed to new developmental and evolutionary forces that determine their body forms. In Nigeria, reports on morphological diversity of fishes within populations of the same species includes studies by Omoniyi and Agbon [23]; Solomon et al [24]; Oladimeji et al [25]; Ukenye et al [26] etc. Length-weight relationship is a crucial growth index used by fishery biologists as a tool for sustainable fisheries management [27].…”
Section: Introductionmentioning
confidence: 99%